Wireless information highways - Katsaros, Dimitrios.; Nanopoulos, Alexandros.; Manolopoulos, Yannis, 1957- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2005)
This book provides an introduction to topics related to the methodologies developed to support data management in asymmetric communication environments. This book is based on a number of self-contained chapters and provides an opportunity for practitioners and researchers to explore the connection between various computer science techniques and develop solutions to problems that arise in the rapidly emerging field of wireless networks.